Understanding teaching behavior through a theoretical perspective of teacher conception: cases in China - Zhu, Fangchun; Xu, Binyan (Frontiers in Education, 2023)
Teaching behavior is a key indicator for analyzing the cognitive factors of teachers. Cognitive factors affect teachers' behavior. The use of technology rebuilds teachers' didactical processes and their cognition in teaching mathematics. This study examined classroom behavior from the perspective of teacher conception and chose the dynamic geometry software (DGS) to analyze how teacher conception affects their daily work by comparing four Chinese mathematics teachers with varying teaching and technology experiences. The results suggested that these teachers were aware of the value of the DGS in teaching and learning mathematics. Although it is still difficult for teachers to move away from the teacher-centered method, some have begun to use the DGS to create new learning situations with which students are not familiar to improve their mathematical skills. Further research is needed to obtain more evidence and generalized conclusions for other situations.